Artificial photons - Mohamad Azzeme, Azzreena; Mohd Sobri, Mohamad Zulfazli; Ramlan, Nurhana Nadia; Md Zawawi, Muhamad Rizal (Universiti Putra Malaysia Press, 2017)
Plants are capable of making their own food through a process called photosynthesis. The process occurs in a specialised cell structure called chloroplast. Inside the chloroplast there is a plant pigment called chlorophyll that absorbs light. People often associate photosynthesis with direct sunlight, but the truth is, artificial lights can also induce photosynthesis. Artificial lights from light emitting diodes (LEDs) carry an array of light intensities and colours that are appropriate for growing plants.